Job-Related Factors And Productivity Of Labour In The Nigerian Public Sector: The Case Of Lamata - Fajana, Sola; Shonuga, Adedoyinsola (Archives of Business Research, 2020)
Productivity has a sustained demonstrable influence on business and political processes and outcomes in all climes. This study explores how the public sector in Nigeria can create ‘decent jobs’ which are more productive and rewarding in all senses. The adopted methodology was positivism which involves figurative or quantitative investigation and communication of observed phenomena. Based on this approach, a questionnaire was designed to gather information from fifty (50) staff in the Lagos Metropolitan Area Transport Authority (LAMATA). Data was analyzed with the use of descriptive statistics, and the Pareto chart and Kano’ Product/Service attribute classification mechanism. The findings were indicative of dominant factors such as opportunities for learning and development (µ=4.4), gifts at special periods (µ=4.7), and pay and rewards (µ=4.5). It was recommended that organizational and institutional policy drivers should continually consider these factors as expressed in the direct and group expectations of the employees in the policy-making and review processes.